The Jurisprudence of the Supremo Tribunal Federal in Brazil’s First Republican Decade and the States of Siege (1889-1898) (Italian Review of Legal History, 2024)
In Brazil’s first republican decade (1889-1899) several difficulties were associated with the birth of the Republic and the stabilization of this new form of government. The very construction of a new Judicial Power. The new Republican Judiciary had to face in the early years successive declarations of a state of siege calling on it to act and respond on the issue, since the Judiciary had the role of guardian of the Constitution and protector of individual rights, particularly the newly created Supreme Court. The Judiciary was therefore mobilized, through habeas corpus petitions, to take a position on the suspension of constitutional guarantees, the constitutionality of the state of siege and its effects. We have analyzed three important points: 1) how the Judiciary acted in relation to the other Powers of the State, particularly the Executive; 2) how it did or did not protect individual liberties during the period of exception; and 3) how the Judiciary exercised its role as guardian of the Constitution by curbing abuses of power. In analyzing this decade, we note the existence of a permanent underlying theme: the political and the legal, the conflict between what is political and what is legal, the difficulty of not mixing the issues and imposing limits on each. The new Judiciary thus sought to distance itself from politics and align itself with its role as guardian of the Constitution.
Keywords: Jurisprudence; state of siege; individual rights; Supreme Tribunal Federal; Brazilian Judicial Power